Literature Review: Aktivitas Batang dan Daun Sambiloto (Andrographis Paniculata Nees) terhadap Target Molekular Terapi Diabetes - Nurul Hidayatul Mar'ah (Fakultas Farmasi Universitas Setia Budi, 2021)
Andrographis paniculata Nees, so-called sambiloto is a plant that is effective as an alternative therapy for diabetes mellitus (DM). Sambiloto is a multi-compound plant that contains diterpenoids, flavonoids and polyphenols. This study aims to explain the activity of chemical compounds contained in the stems and leaves of sambiloto against five molecular targets for DM therapy, namely Dipeptidyl Peptidase 4 (DPP4), Protein Tyrosine Phosphatase (PTP1B), α-glucosidase, Glucose Transporter (GLUT) and glucokinase. This study uses a systematic review method by making PRISMA checklists and flow diagrams, determining inclusion-exclusion criteria, search engines and keywords to get relevant data. The data is obtained from the primary research results presented in the data extraction table, and then is analyzed comprehensively. The results of the study are: the diterpenoids and flavonoids can provide activity against molecular targets, such as 19-triphenyl isoandrographolide which can inhibit DPP4, α-glucosidase and activate glucokinase; andrographolactone can inhibit PTP1B; deoxyandrographolide increase translocation and acceleration of GLUT4; 15-p-methoxybenziliden 14-deoxy-11,12-didehydroandrographolide inhibits α-glukosidase; and flavonoid groups such as apigenin compounds can inhibit DPP4, PTP1B, and activate glucokinase.